Sustainable food system country profiles for low- and middle-income countries. Methodology outline - Béné, Christophe; Lundy, Mark M.; Prager, Steven D.; Chege, Christine Gacheri Kiria; Hernández, Ricardo; Wiegel, Jennifer Rebecca; Achicanoy Estrella, Harold Armando; Arias, Diana Carolina (2022)
There is a need to find a “middle ground” whereby the complexity, dynamic, and multi-sectoral/multi-actors nature of food systems is captured and boiled down to a handful of key indicators that help prioritize entry points for interventions. Furthermore, the process of identifying those selected indicators needs to follow a clear, transparent, and reproducible protocol/methodology so that comparison between countries (and over time) is also possible. The ambition of the “Sustainable Food System Country Profile” project is to design, field-test and demonstrate the feasibility of such a “middle ground” approach, initially in three countries (Bangladesh, Ethiopia and Honduras). The final product, which will include this protocol plus three Food System Country Profiles, will offer a tool to facilitate more informed and evidence-supported decisions around food systems. We envisage that this tool will form part of the “SFS Toolbox” of the One Planet (10YFP) Sustainable Food Systems (SFS) Programme and will then pave the path for the development of similar country profiles in a larger number of low- and middle-income countries (LMICs) in the near future.